Perencanaan Strategis dalam Pengembangan Lembaga Pendidikan Islam - Ahmadi; Alghazali Dilara; Zainal Abidin; Hekrian Sepga; Mahrawi Mahrawi; Samsudin Bakar; Irma Yulianti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze strategic planning in the development of Islamic educational institutions, focusing on strategy formulation, program implementation, and the supporting and inhibiting factors affecting institutional development. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and document analysis involving institutional leaders, educators, foundation administrators, and relevant stakeholders. Data were analyzed interactively through data reduction, data display, and conclusion drawing. The findings indicate that strategic planning is implemented through four main stages: internal and external environmental analysis, formulation of strategic vision and objectives, implementation of development programs, and continuous evaluation. Successful strategy implementation is supported by visionary leadership, stakeholder participation, an adaptive organizational culture, and the capacity to respond to change. In contrast, limited resources, resistance to change, and weak monitoring systems constitute major obstacles. These findings highlight the importance of adaptive, participatory, and sustainable strategic planning in strengthening the development of Islamic educational institutions. The study contributes to the strategic management literature by emphasizing institutional adaptability and stakeholder engagement as essential elements of sustainable educational development